Interview 7 - Abubakari, Yushawu
This file contains the interview notes with Kinger. Kinger (pseudonymized) is 26 years old and high school graduate. He is single with 5 siblings and without a father. He has been in the scamming industry for 4 years. Kinger is a middle scammer: people work under him, and he also work under others. The interview was conducted in a restaurant.